Effects of the neonicotinoid insecticide, clothianidin, on the reproductive organ system in adult male rats - Bal, Ramazan; Turk, Gaffari; Tuzcu, Mehmet; Yilmaz, Okkes; Kuloglu, Tuncay; Baydas, Giyasettin; Tuzcu, Zeynep (Informa Healthcare, 2013)
Clothianidin (CTD) is a novel, broad-spectrum insecticide. In the current study, it was aimed to study the effect of subchronic exposure to low doses of CTD (2, 8 and 24 mg/kg body weight/day) on the reproductive system in adult rats. CTD treatment did not significantly change serum testosterone level or sperm parameters (e. g. concentration, motility and morphology), but caused significant decreases in weights of epididymis, right cauda epididymis and seminal vesicles. CTD treatment did not cause sperm DNA fragmentation and did not change the apoptotic index in the seminiferous tubules and levels of alpha-tocopherol and glutathione, but increased the level of thiobarbituric acid-reactive substances and cholesterol levels significantly at all doses. CTD exposure caused significant elevations in palmitic, linoleic and arachidonic acids in testis in all CTD-exposed groups. There was a drop in 20:4/18:2 (arachidonic acid/linoleic acid) ratio and an increase in 18:1n-9/18:0 (oleic acid/stearic acid) ratios in all CTD groups, in comparison to the control group. In conclusion, CTD had little detectable detrimental effects on the reproductive system of male rats over the measured parameters.
Keywords: Apoptosis; clothianidin; DNA fragmentation; fatty acid composition; lipid peroxidation; sperm characteristics